Uncovering the Unsung Hero of Sulu: Panglima Sayyadi’s Character Archetypes in Kissa - Nelson S. Dino; Mary Joyce Z. Guinto-Sali,; Al-Haniff Lee Matolo; Asmiaty Amat; Sajed S. Ingilan (University of Southeastern Philippines, 2023)
This study explores Panglima Sayyadi, the Tau Sug hero of Tapul Island, Sulu, Philippines, whose account was obtained from a kissa, an oral narrative passed down through generations in an unstructured form. It analyzes the character archetypes of the Tau Sug Hero to investigate his disposition as the commanding leader of the Sulu Forces against the colonizers’ imposition, as depicted by the old Tau Sug folks who recall his history. To reveal his characteristics, an archetypal literary criticism is employed in this study, which examines three classified character archetypes: The Ego Types, The Self Types, and The Soul Types. The results indicate that Panglima Sayyadi’s character was an amalgamation of the three motifs, being the Warrior and the Traditionalist of the Ego Type, the Leader and the Thinker of the Self Type, and the Revolutionary and the Visionary of the Soul Type, which implies his courage to defend and loyalty to his belief system. It can also be concluded that these archetypes are innate to his individuality as a Tau Sug.